The Influence of Counselor Empathy, Student Sex, and Grade Level on Perceived Counselor Role - Conklin, R. C.; Nakoneshny, Maurice (Canadian Journal of Counselling and Psychotherapy, 2012)
This research project, using Truax's Scale for the Measurement of Accurate Empathy and an adapted version of Warman's Counsel- ing Appropriateness Check-List, attempted to investigate the relationship between counselor empathy and student perception of counslor role. Results of the study indicated that counselors rated "high" in empathy were considered to be significantly more appropriate persons to consult for advice for personal-social problems than counselors rated "low." No significant differences were obtained for educational-vocational problems. Female students in contrast to males considered the counselor to be signifi- cantly more appropriate for discussion of both problem areas. Grade 9 students considered the counselor to be significantly more appropriate for discussion of educational-vocational concerns than did grade 7 or grade 8 stLidents. The results of this study and their implications were briefly discussed.